(3JHGjf GdGgOGa GdeJhNGI ef JHfj GdeSDhdjI GdGLJeGYjI aj GdefXeGJ GdMchejI h GdNGUIs - (3fYeI YHGS(B, (3GdNaGLjs; (3WGgQ eMSf GdZGdHj(B, s ((3YeGf(B:s (3OGQ GdjGRhQj(B,s, 2008)
(3GdMGcejI h GdefXhQ GdCNdGbj dgG aj GdeDSSGJ, GdLhOI , GdYbd GdGOGQj , GdQjGOI h QCS GdeGd GdeYQaI , GdNWQ , GdCNdGb h GdeSDhdjI GdGLJeGYjI (B.s
(3eQGLY U(B.355s
Keywords: (3GdEOGQI GdYGeIs; (3GdeSDhdjI GdGLJeGYjIs; (3GdefXeI GdMchejIs